# Calculator search results

Formula
Solve the equation
Calculate the differentiation
Graph
$y = \dfrac { 1 } { 2 } x - 1$
$x$-intercept
$\left ( 2 , 0 \right )$
$y$-intercept
$\left ( 0 , - 1 \right )$
$y = \dfrac{ 1 }{ 2 } x-1$
$x = 2 y + 2$
 Solve a solution to $x$
$y = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ x } - 1$
 Calculate the multiplication expression 
$y = \color{#FF6800}{ \dfrac { x } { 2 } } - 1$
$\color{#FF6800}{ y } = \color{#FF6800}{ \dfrac { x } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ 2 } \color{#FF6800}{ y } = \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$2 y = \color{#FF6800}{ x } - 2$
 Move $x$ term to the left side and change the sign 
$2 y - x = - 2$
$\color{#FF6800}{ 2 } \color{#FF6800}{ y } - x = - 2$
 Move the rest of the expression except $x$ term to the right side and replace the sign 
$- x = - 2 \color{#FF6800}{ - } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ y } \right )$
$- x = \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ y } \right )$
 Organize the expression 
$- x = \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ - } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
 Change the sign of both sides of the equation 
$x = 2 y + 2$
$\dfrac {d } {d x } {\left( y \right)} = \dfrac { 1 } { 2 }$
Calculate the differentiation of the logarithmic function
$\dfrac {d } {d \color{#FF6800}{ x } } {\left( \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right)}$
 Calculate the differentiation 
$\color{#FF6800}{ \dfrac { 1 } { 2 } }$
 그래프 보기 
Linear function
Solution search results